TRADISI PESANTREN SEBAGAI BASIS PEMBENTUKAN KARAKTER SANTRI DI TENGAH ARUS MODERNISASI DAN PERUBAHAN SOSIAL - Agustina Suryani; Tasya Nadira (Jurnal Ekshis, 2025)
This study examines how pesantren traditions contribute to the formation of students’ character amid rapid modernization and digital transformation. The research aims to identify the traditional practices that shape students’ religious, social, and moral values, as well as to explore the adaptive strategies implemented by pesantren to maintain their relevance in contemporary society. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation to understand the mechanisms of value internalization within daily routines and communal life in pesantren. The findings reveal that religious activities, disciplined routines, and the role of the kyai are central to character formation, while modernization pressures demand adaptive responses. The study concludes that pesantren remain effective character-building institutions through their ability to preserve core traditions while integrating contextual innovations.